Comparative study between Laparoscopic Trasabdominal Preperitoneal (TAPP) inguinal hernia repair and open mesh repair in Medical city. - Fadhel, Muayad A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Inguinal hernias are a common medical problem that can significantly decrease the quality of life.Repair of inguinal hernia is one of the commonest surgical procedures worldwide irrespective of the country, race, or socioeconomic state. The inguinal hernia repair has been a controversial area in surgical practice from the time it has been conceived. Laparoscopic inguinal hernia repair has shown a great deal of promise as a treatment for the condition.Objectives: To compare the outcome of laparoscopic versus open inguinal hernia mesh repair in terms of operative time , analgesics requirement , postoperative complication , hospital stay and return to daily activities and work.Patients and methods: A prospective study of 80 patients with inguinal hernia repair, carried out during the period from January 2010 till January 2013, Baghdad Teaching Hospital\Medical City, Iraq, to compare the effectiveness and safety of laparoscopic and conventional open mesh techniques. Those patients were divided into 2 groups (each group of 40 patients); 1st group treated by laparoscopic (TAPP) repair and the 2nd one by open technique (mesh repair).Results: The mean operating time in laparoscopic repair was 55 minutes (45-120) while in open repair it was 38 minutes (30-110) .The laparoscopic repair was superior to open repair in regard to ; less analgesic requirement post operatively , short hospital stay , and faster return to daily activities and workThere was no statistically significant difference between the two groups regarding complications.Conclusion: Laparoscopic hernia repair is equally safe and can provide less postoperative morbidity in experienced hands Therefore laparoscopic hernia repair can be safely recommended for most cases of inguinal hernia unless laparoscopy itself is contraindicated.